Maturation of scFv 80r for the Neutralization of SARS-CoV-2 RBD using Ribosome Display - Langer, Ian. (Tufts University. Tisch Library., 2021)
Thesis (M.S.)--Tufts University, 2021.; Submitted to the Dept. of Pharmacology and Drug Development.; Advisor: Alex Bohm.; Keywords: Pharmacology, Biochemistry, and Biomedical engineering.